Strategi Desain Integrasi Rumah Susun dan Fasilitas Pertanian Perkotaan berbasis Self-sufficiency - Abhinaya Ramadhikka; Ofita Purwani; Sri Yuliani (Universitas Sebelas Maret Surakarta, 2023)
This paper focuses on the implementation of the concept of self-sufficiency in energy and food into residential buildings by adding agricultural facilities. There is still no specific literature on the application of self-sufficiency in residential buildings with urban agricultural facilities. Current literature. The current literature discusses self-suffiency in general, or the application of one aspect of self-suffiency in buildings, such as energy. In addition, the scale of discussion on large-scale self-sufficiency and not specific to residential buildings with urban agricultural facilities Therefore, this article can be one of the literature that discusses self-sufficiency specifically in residential buildings with urban agricultural facilities and on a microscale. Using theories from Mahdi, Magdalenna and Suharyanto , we formulate how to apply the self-sufficiency concept to the residential building by calculating the food and energy needed by the residents and how to achieve it. This project is a model of how to achieve self-sufficiency in residential buildings